2023
DOI: 10.1002/advs.202300121
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Antigen Source: Cancer Vaccines Based on Whole Tumor Cell/tissue Lysate or Whole Tumor Cell

Abstract: Cancer immunotherapies have improved human health, and one among the important technologies for cancer immunotherapy is cancer vaccine. Antigens are the most important components in cancer vaccines. Generally, antigens in cancer vaccines can be divided into two categories: pre-defined antigens and unidentified antigens. Although, cancer vaccines loaded with predefined antigens are commonly used, cancer vaccine loaded with mixed unidentified antigens, especially whole cancer cells or cancer cell lysates, is a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 235 publications
0
23
0
1
Order By: Relevance
“…Leukemia‐derived DCs and monocyte‐derived DCs (Mo‐DCs) are the two primary DC types used in DC vaccines. Phase I, II, and III clinical trials have investigated DC cancer vaccines because it is feasible to cultivate DCs in enough quantities 20–22 …”
Section: Cancer Vaccine Platform Typesmentioning
confidence: 99%
“…Leukemia‐derived DCs and monocyte‐derived DCs (Mo‐DCs) are the two primary DC types used in DC vaccines. Phase I, II, and III clinical trials have investigated DC cancer vaccines because it is feasible to cultivate DCs in enough quantities 20–22 …”
Section: Cancer Vaccine Platform Typesmentioning
confidence: 99%
“…The results have shown that WTCs vaccines are more successful in eliciting immune responses to cell surface antigens than their soluble or split counterparts [ 59 ]. Scientists have explored different approaches to optimize whole-cell vaccines and improve their immunogenicity [ 60 ]. These include using intact tumor cells, which are nonviable but maintain their structure, and tumor cell lysates, which are nonviable and have disrupted structures [ 61 ].…”
Section: Tumor Vaccinesmentioning
confidence: 99%
“…Moreover, traditional vaccines elicit humoral immunity, whereas cellular immunity mediated by the CD8 + cytotoxic T lymphocytes (CTLs) plays a key role in killing cancer cells for cancer vaccines ( 9 , 10 ). A variety of strategies have been developed to increase the efficacy of the vaccine by application of the whole-tumor lysate ( 11 ), coadministration of antigens with adjuvants ( 12 , 13 ), and formulation in carriers ( 14 ). Nanocarriers are recognized as promising delivery vehicles for cancer vaccines, which facilitate targeted delivery of antigens to essential immune organs and cell types ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%